Implementasi Manajemen Kelas dalam Meningkatkan Minat Belajar Siswa pada Pembelajaran PAI Kelas XI Film di SMKN 1 Solok - Aisyah Oktafiyani; Rini Rahman (AS-SABIQUN, 2022)
Classroom management is an effort to manage students in the classroom which is carried out to build and maintain an atmosphere or class condition that supports learning programs by creating and maintaining the enthusiasm of students to always be actively involved and take part in the educational process at school. The formulation of the problem set out in this study is what class management plans are in increasing student interest in learning in PAI learning for class xi film at SMKN 1 Solok. The purpose of this study is to describe classroom management planning in increasing student interest in learning PAI class xi film at SMKN 1 Solok. This research is a qualitative research with descriptive type. The data in this study the authors obtained by using the techniques of observation, documentation and interviews. The data obtained from the study were then analyzed by data reduction, data presentation, and drawing conclusions. The results showed that before carrying out learning the teacher had to do planning, when planning class management in increasing student interest in learning PAI including, the teacher needed to prepare learning tools that were used as guidelines or references in carrying out learning. This learning tool consists of compiling a syllabus, preparing a lesson planning plan (RPP) in accordance with the applicable curriculum, providing interesting learning media according to the material to be taught, reviewing the material to be taught in order to master what is conveyed, making other device programs. such as semester programs, annual programs, educational calendar analysis, KI/KD analysis and compiling other instruments that are deemed necessary.